Pengaruh Kartu Pintar Ibu Terhadap Kewaspadaan Ibu Pada Anak Diare Masa Pandemi Covid-19 di Lubuklinggau - Sapondra Wijaya; Wahyu Dwi Ari Wibowo; Susmini Susmini (Sekolah Tinggi Ilmu Kesehatan Kesdam IX/Udayana, 2022)
Background: The spread of Covid-19 during a pandemic is a problem that is of the utmost concern. One of the activities that are at risk of being infected with Covid-19 is going out of the house and visiting health facilities which are the most frequently done. One of the groups who are susceptible to disease are children. Many diseases that often occur in children, including diarrhea. When a child has diarrhea, mother will take the child to a health facility, even though there are the prone place to Covid-19 transmission. Therefore, there is a need for socialization about mother’s vigilance of diarrhea in children at home, so that mothers can make the best decisions for their children. Purpose: The purpose of this study was to determine the effect of the Mother's Smart Card, which is a simplification of the MTBS book, on maternal vigilance in the management of children with diarrhea in the pre-hospital phase. Methods: This study used a quasi-experimental design with a pre and post-test approach with purposive sampling technique on 30 mothers. Mother's vigilance is measured by the way the mother behaves and the mother's accuracy in making decisions when the child has diarrhea. The measurement uses a questionnaire Results: The results of data analysis using paired t-test showed that there was a significant effect of the Mother's Smart Card on maternal alertness in the management of children with diarrhea at home with a p value of 0.000. Conclusion: This means that the Mother's Smart Card can increase mother's vigilance in the management of pre-hospital child diarrhea. With this result, it is hoped that the Smart Mother Card can be a reference in increasing mother’s vigilance, and minimizing treatment at inappropriate health facilities that can put the risk of Covid-19 transmission at risk.